Efficacy of electro-acupuncture on pregnancy outcomes for women undergoing in vitro fertilization: study protocol for a pilot randomized controlled trial - Zheng, Xiaoyan; Ji, Ran; Li, Chaoliang; Zhu, Hao; Jiang, Ziyi; Zhang, Jingwen; Su, Yang; Yu, Siyi; Yu, Zheng; Lv, Xingyu; Liang, Fanrong; Yang, Jie (Frontiers in Endocrinology, 2024)
This study is the first to provide information about the effectiveness and safety of electroacupuncture (EA) treatment for infertile women undergoing in vitro fertilization (IVF). The study compares EA versus placebo EA and a control group.The study will use a rigorous methodology to reduce the risk of bias, including adequate randomization, quality control, and blinded outcome assessors and statisticians. Eligible participants will be strictly recruited and screened, and a standard operating procedure will be conducted rigorously to ensure quality control. Due to the nature of acupuncture, only EA and pEA group participants can be blinded.Treatment providers are likely to bring bias and influence the results.